Obtenção de alumina a partir de latas de alumínio utilizando diferentes digestões e 8-hidroxiquinolina como agente quelante - Ekawa, Bruno (2016)
Aluminum cans has wide uses and Brazil is among one of the world's largest country at recycling, to provide an option that adds value to raw materials, this paper uses aluminum cans as aluminum source for the production of alumina. Evaluating the use of acid digestions (hydrochloric acid, sulfuric acid and aqua regia) and basic (potassium hydroxide) to solubilize the aluminum after which will be complexed with 8-hydroxyquinoline at different pH's. By calcination, the complex produces an oxide with metal components with varying proportions depending on the digestion process. The thermal behavior of the complex varies with the morphology and metals present, occurring different events due to these characteristics.